Finite element analysis on parameterized model of fiber composite battledore - Shen, H (The International Journal of Multiphysics, 2019)
Composite materials have superior properties than single materials, and they have been applied in many fields, for example, sporting goods. In this paper, a battledore was manufactured using fiber composites, and finite element analysis was carried out. The parameterized model of the battledore was established by ANSYS finite element software. Then the displacement, stress and failure of the battledore were analyzed. The results showed that the maximum displacement of the battledore was about 0.9 mm, located at the top of battledore frame, the maximum stress was about 155 MPa, located at the junction of battledore frame and rod, and the maximum failure factor was 0.38, which is higher than that of common aluminum alloy battledore. All the findings suggested that the designed battledore was effective. The battledore has a high safety factor and is worthy of application in practice.